Enzymatic Hydrolysis and Fermentation of Banana Pseudostem Hydrolysate to Produce Bioethanol - Lesetja Moraba Legodi; Daniel Coenrad LaGrange; Elbert Lukas Jansen van Rensburg; Ignatious Ncube (International Journal of Microbiology)
Banana pseudostem (BPS) is an agricultural waste with a high holocellulose content, which, upon hydrolysis, releases fermentable sugars that can be used for bioethanol production. Different pretreatment methods, namely, 3% (w/v) NaOH, 5% (v/v) H2SO4, and liquid hot water, applied on the BPS resulted in the availability of 52%, 48%, and 25% cellulose after treatment, respectively. Saccharification of the pretreated BPS with 10 FPU/g dry solids (29.3 mg protein/g d.s) crude enzyme from Trichoderma harzianum LMLBP07 13-5 at 50°C and a substrate loading of 10 to 15% released 3.8 to 21.8 g/L and from T. longibrachiatum LMLSAUL 14-1 released 5.4 to 43.5 g/L glucose to the biomass. Ethanol was produced through separate hydrolysis and fermentation (SHF) of alkaline pretreated BPS hydrolysate using Saccharomyces cerevisiae UL01 at 30°C and 100 rpm. Highest ethanol produced was 17.6 g/L. Banana pseudostem was shown as a potentially cheap substrate for bioethanol production.